INFORMATION SYSTEM AS A SERVICE: ISSUES AND CHALLENGES - Muhammad Hafizhuddin Hilman (Faculty of Computer Science Universitas Indonesia, 2012)
Information system evolved as the evolution of information technology. The current state of information technology, placed the internet as a main resources of computing. Cloud technology as the backbone of internet has been utilized as a powerful computing resources. Therefore, cloud introduced new term of service oriented technology, popular with “as a service” kind of name. In this paper, the service oriented paradigm will be used to address future trend of information system. Thus, this paper try to introduce the term “information system as a service”, holistic view of infrastructure as a service, platform as a service, software as a service, and data as a service